PENGARUH KOMPENSASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA DINAS LINGKUNGAN HIDUP KOTA PALEMBANG - RM Rionaldi Bakrie; Riswan Jaenudin (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study analyzes the effect of compensation on employee productivity at the Environmental Agency of Palembang City. Methods: The sample included 70 employees from three categories: Civil Servants (PNS), Government Contract Employees (PPPK), and Honorary Staff. Data were collected through validated questionnaires (27 items for compensation, 20 items for productivity), in-depth interviews with 7 employees, and document analysis. Instrument validity and reliability were tested using product moment correlation (validity) and Cronbach’s alpha (reliability), with reliability coefficients exceeding 0.7 for both variables. Questionnaire results revealed 54.3% of respondents rated compensation as "very high," while 58.57% rated productivity as "very high." The Pearson product moment correlation test yielded a strong positive correlation (r = 0.677), indicating a significant relationship between compensation and productivity. Results: The coefficient of determination (R² = 45.83%) demonstrated that compensation accounts for 45.83% of productivity variation, with the remaining 54.17% influenced by other factors. Hypothesis testing using a t-test resulted in a t-value = 10.3, significantly higher than the critical value = 2.000 (α = 5%), leading to the acceptance of the alternative hypothesis (Ha). This confirms that compensation has a impact on employee productivity. Keywords: Compensation, Employee Productivity